Protection against age-dependent renal injury in the F344xBrown Norway male rat is associated with maintained nitric oxide synthase - Moningka, Natasha C. (2010)
Age-dependent renal damage is influenced by genetic background and the Fisher344xBrown Norway (F344xBN) rat is resistant to glomerular injury. In vulnerable strains, a fall in renal nitric oxide synthase (NOS) contributes to age-dependent renal damage. Here, we investigated renal NOS in young (3 months) and old (30 months) male F344xBN to test the hypothesis that renal NOS is maintained in “protected” strains. We also examined if 6 months of renin-angiotensin system (RAS) blockade using angiotensin converting enzyme inhibition (ACEI) and angiotensin receptor blockade (ARB) provides further benefit in these “protected” old rats. Aging increased tubulointerstitial injury but glomerular sclerosis was minimal and NOS and superoxide dismutase abundance increased. There was no change in the NOS inhibitor, ADMA (asymmetric dimethylarginine) or its regulatory enzymes. RAS blockade with ARB protected against tubulointerstitial injury and increased nNOSα, but ACEI, which also increased nNOSα, had no protective effect on the tubulointerstitium. We conclude that the glomerular sclerosis-resistant aged male F344xBN rat maintains renal NOS, thus reinforcing our hypothesis that progressive glomerular injury is related to renal NOS deficiency. The tubulointerstitial injury seen with aging is reversed with 6 months of ARB but not ACEI and is not associated with renal NOS.